Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Federal Internasional Finance (FIFGROUP) Cabang Duren Jaya Bekasi - Roddyan Alianissa; Hasanuddin (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The Effect of Work Environment and Work Motivation on Employee Performance at PT. FIFGROUP Duren Jaya Bekasi Branch. This research aims to measure the influence of the work environment and work motivation on employee performance at PT. FIFGROUP Duren Jaya Bekasi Branch. The sampling technique used in this research used saturated samples. The data collection tool in this research used a questionnaire with 52 respondents. The design used in this research is testing using SPSS for Windows version 26. The results of this research show that the work environment has a significant effect on employee performance, work motivation has a significant effect on employee performance the work environment and motivation work has a significant effect on the performance of PT FIFGROUP employees This research provides suggestions to PT. FIFGROUP Duren Jaya Bekasi Branch to be able to pay more attention to work space facilities, and provide work motivation to its employees so that employee performance increases.